2010
DOI: 10.1375/twin.13.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviour of Women With Twin Pregnancies

Abstract: It has been assumed that sexual activity during pregnancy would lead to an increased risk for miscarriage and other complications of pregnancy. Various studies showed no association of sexual behavior and pregnancy complications in single pregnancies. The aim of our study was to evaluate changes in sexual activity in women with twin pregnancies and whether a higher frequency of sexual intercourse was associated with an increased risk for pregnancy complications. We report on 50 women with twin pregnancies who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Stammler-Saffar et al also stresses the importance of concerns and fears. It should be remembered that assisted reproductive patients are even more concerned about the course of pregnancy and fetal well-being as not only the fertilization had been long-awaited, but they have had to cope with many obstacles to achieve this goal [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stammler-Saffar et al also stresses the importance of concerns and fears. It should be remembered that assisted reproductive patients are even more concerned about the course of pregnancy and fetal well-being as not only the fertilization had been long-awaited, but they have had to cope with many obstacles to achieve this goal [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the risk of preterm birth within 72 h after premature rupture of membranes in twin pregnancy is greater than that in singleton pregnancy 17 , which is related to factors such as reproductive tract infection, increased amniotic pressure, and uneven force on fetal membranes 18 . Therefore, for the prevention of premature rupture of membranes and active treatment of premature rupture of membranes, delaying the gestational age as much as possible is suggested in order to reduce the occurrence of premature birth in twin pregnancy, strict monitoring of reproductive tract infection during pregnancy, avoid strenuous activities in the late stage 19 , prohibit sexual life 20 , and develop a healthy lifestyle habits 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A twin pregnancy differs little from a singleton pregnancy, except for the duration, with childbirth on average taking place at 37 weeks. According to the limited research in this area, sexuality does not influence the onset of birth [14]. So, without complications, the instructions and recommendations on sexuality can be the same.…”
Section: Multiple Gestationmentioning
confidence: 99%